Aksesibilitas Pelayanan Sistem Informasi Manajemen pada Dinas Perpustakaan dan Kearsipan Kabupaten Gorontalo - Panji Sukma; Robin Pakudu; Sakbir Sakbir; Umar Sako Baderan (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This study aims to describe the Accessibility of Management Information System Services at the Library and Archives Service of Gorontalo Regency. The research method uses a qualitative approach. The results of the study indicate that the Accessibility of Management Information System Services at the Library and Archives Service of Gorontalo Regency has not been running well, where of the three indicators measured there are two indicators that are not fully optimal, namely data access time and data accuracy, this can be seen from the many complaints from service users about the slow responsiveness of data or information needed by service users and frequent errors or inconsistencies between the data or information needed by service users and what is presented by the Management Information System. While one other indicator, namely access flexibility, is considered optimal, this can be seen from the time and method of the information access process which can really adjust to the conditions of service users, namely it can be accessed anytime and anywhere and in any way such as accessed via laptop, computer or smartphone.